Zoological Letters - Kuratani, Shigeru
Zoological Letters is an open access journal that publishes new and important findings in the zoological sciences. As a sister journal to Zoological Science, Zoological Letters covers a wide range of basic fields of zoology, from taxonomy to bioinformatics. We also welcome submissions of paleontology reports as part of our effort to contribute to the development of new perspectives in evolutionary zoology. Our goal is to serve as a global publishing forum for fundamental researchers in all fields of zoology.